Analysis of the Relationship between Digital Literacy Program Development and Lecturer Productivity in Higher Education - Juliastuti; Suherman; Aceng Hasani (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The rapid development of digitalization and technology forces the awareness of digital literacy to be in a strategic and vital position as a tool to enhance the academic productivity of lecturers. This study analyzes the relationship between digital literacy and academic productivity among lecturers at Sekolah Tinggi Agama Islam Tangerang Raya. Digital literacy encompasses access, processing, and utilization of information technology to support academic tasks. This research employs biometric analysis methods to gather data on lecturers’ digital behaviour, including the frequency of digital device usage and access to online academic resources. The findings reveal a significant positive correlation, where lecturers who frequently use digital devices experience a 25% increase in academic productivity in scientific publications. Additionally, the study highlights that active participation in webinars and online courses contributes to improvements in the quality and quantity of research output. Recommendations for institutions include the importance of providing comprehensive training programs focused on data analysis software, reference management, and online academic writing to enhance research efficiency. Furthermore, improving access to online academic resources and providing adequate digital devices will strengthen academic performance. Increasing digital literacy focused on technological capabilities not only significantly enhances the academic productivity of lecturers but also serves as an effective solution for improving other competencies, such as research productivity and scientific collaboration, to achieve more optimal institutional outcomes.